Trust based Multipath Routing Scheme (TMAODV) - Raza Khan, Nikhat; Sharma, Sanjay; Patheja, PS (International Journal of Computer Sciences and Engineering, 2025)
Malicious nodes in MANETS can make considerable damage. As basic routing protocols does not provide any strong security against internal attacks nodes, they can easily become part of network and degrade the performance by launching attack.In this work, the main focus is to develop a method of security in communications between ad-hoc network nodes. This proposed model i.e Trust based Multipath Routing Protocol Scheme (TMAODV), firstly calculates transmission cost and then trust factor is calculated on the basis of number of packets forward and dropped. For this a new data structure is added into neighborhood table. Secondly, a different computation factors like Optimal Traffic Ratio, Remaining Energy value and transmission cost is calculated and this data structure is stored by routing table.